Rheumatoid interstitial lung disease in Canterbury New Zealand: prevalence, risk factors and long-term outcomes—protocol for a population-based retrospective study. Issue 4 (5th April 2022) - Farquhar, Hamish; Beckert, Lutz; Edwards, Adrienne; Matteson, Eric L.; Thiessen, Rennae; Ganly, Edward; Stamp, Lisa K.
Abstract : Introduction: Rheumatoid arthritis (RA) affects approximately 0.5%–1% of the general population. Clinically significant interstitial lung diseases (ILD) develops in just under 10% of people with RA, and subclinical disease is more common. Little is known about RA-ILD in New Zealand (NZ), or the number of persons with RA in Canterbury, NZ. This study aims to determine: (1) incidence and prevalence of RA, (2) incidence and prevalence of RA-ILD, (3) clinical characteristics and risk factors for the development of RA-ILD, (4) long-term outcomes of RA-ILD, in the population resident within the Canterbury District Health Board (CDHB) catchment area. Methods and analysis: Persons aged 18 years of age and older, and resident in the region covered by the CDHB with RA as well as RA-ILD will be identified by retrospective review of medical records. Prevalent as well as incident cases of RA between 1 January 2006 and 31 December 2008 and between 1 January 2011 and 31 December 2013 will be identified, and followed until 30 June 2019. Existing as well as incident cases of RA-ILD during this time will be identified. The association between the development of ILD and clinical characteristics and environmental exposures will be examined using Cox-proportional hazard models. Kaplan-Meier methods will be used to estimate survival rates for patients with RA-ILD. Mortality for people with RA and RA-ILD will also be compared with the general population of the CDHB. Ethics and dissemination: Data will be obtained by retrospective review of medical records. Deidentified patient data will be stored in a secure online database. Data on individual patients will not be released, and all results will only be published in aggregate. Ethical approval has been obtained from the University of Otago Human Research Ethics Committee (REF HD18/079). Results will be published in peer-reviewed medical journals and presented at conferences. Trial registration number: ACTRN12619001310156; Pre-results.